Kawasaki Disease Hospitalizations in the United States 2016–2020: A Comparison of Before and During the Coronavirus Disease 2019 Era. Issue 11 (10th August 2021) - Phamduy, Timothy T.; Smith, Sharon; Herbst, Katherine W.; Phamduy, Paul T.; Brimacombe, Michael; Hogan, Alexander H.; Salazar, Juan C.; Sturm, Jesse
Abstract : Background: Kawasaki disease (KD) is an acute vasculitis of young children. A comparison of US hospitalization rates and epidemiologic features of KD in 2020 to those of precoronavirus disease years has yet to be reported. Methods: Using a large, inpatient database, we conducted a retrospective cohort study and analyzed data for patients with (1) diagnosis coding for KD, (2) IV immunoglobulin treatment administered during hospitalization and (3) discharge date between January 1, 2016, and December 30, 2020. Severe cases were defined as those requiring adjunctive therapy or IV immunoglobulin–resistant therapy. Results: The annual number of KD hospitalizations were stable from 2016 to 2019 (n = 1652, 1796, 1748, 1692, respectively) but decreased in 2020 (n = 1383). KD hospitalizations demonstrated seasonal variation with an annual peak between December and April. A second peak of KD admissions was observed in May 2020. The proportion of KD cases classified as severe increased to 40% in 2020 from 33% during the years 2016–2019 ( P < 0.01). Median age in years increased from 2.9 in subjects hospitalized from 2016 to 2019 to 3.2 in 2020 ( P = 0.002). Conclusions: Compared with the previous 4 years, the annual number of pediatric KD admissions decreased, and children discharged with diagnostic codes for KD in 2020 were generally older and more likely to have severe morbidity possibly reflective of misdiagnosed multisystem inflammatory syndrome in children. Clinicians should be wary of a possible rise in KD rates in the postcoronavirus disease 2019 era as social distancing policies are lifted and other viruses associated with KD return.